Silver Burdett making music.[kit] - Beethoven, Jane. (Glenview, Ill. : Scott Foresman, 2002)
This program presents sequenced instruction in elements and skills, as well as connection to other discplines in every lesson ... The themes are coordinated from grade to grade so that students at different levels can share a related theme in their instruction." (teacher's edition pp. T8-T9).
Keywords: Music -- Instruction and study -- Juvenile; School songbooks